Reference Pricing and Parallel Imports: Evidence from Germany - Laura Birg (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
I study the effect of reference pricing on competition by parallel imports, in particular the market share of parallel imports and the number of parallel traders. First, I analyze the effect of reference pricing on competition by parallel imports in a vertical differentiation model with a locally sourced version and a parallel import offered by n identical parallel traders. Second, I explore the effect of reference pricing on competition by parallel imports using a dataset with prescription drugs with competition from parallel imports. Both model and estimation results suggest that the introduction of reference pricing inreases the market share of the parallel import and the number of parallel traders, while a decrease in the reference price decreases the market share of the parallel import and the number of parallel traders.
Keywords: F12; I11; I18; 330; reference pricing; parallel imports; pharmaceutical regulation